2017
DOI: 10.15453/2168-6408.1349
|View full text |Cite
|
Sign up to set email alerts
|

Joint Attention and Occupations for Children and Families Living with Autism Spectrum Disorder: A Scoping Review

Abstract: Background:Research reports that children living with autism spectrum disorder (ASD) may demonstrate deficits in social, emotional, behavioral, and communication skills, which adversely affect social participation and occupational engagement. Joint attention skills constitute any nonverbal communication that captures the attention of another to create a shared interactional experience. The components of joint attention can be targeted through intervention to promote occupational engagement in childhood co-occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
(115 reference statements)
1
12
0
Order By: Relevance
“…RJA is expressed through gaze-following towards the external element, taking the action implied by the IJA or otherwise acknowledging the IJA (Mundy, 2018). RJA is considered a more fundamental skill involving monitoring the social partner, while IJA is considered a more complex skill involving creating a shared social experience (Eschenfelder and Gavalas, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…RJA is expressed through gaze-following towards the external element, taking the action implied by the IJA or otherwise acknowledging the IJA (Mundy, 2018). RJA is considered a more fundamental skill involving monitoring the social partner, while IJA is considered a more complex skill involving creating a shared social experience (Eschenfelder and Gavalas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Through repeated use of JA, children develop understanding of their social partner’s perspectives and learn to share their own perspectives, and, over time and practice, social reciprocity emerges. Because of its key role in supporting social aspects of occupational performance, it is a frequent target for intervention by occupational therapists (Eschenfelder and Gavalas, 2017). A recent scoping review examining the impact of teaching JA strategies on engagement in occupation and co-occupation for children and families with ASD concluded that teaching JA strategies supports engagement in occupations, and in co-occupations with parents (Eschenfelder and Gavalas, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, all 47 articles that remained were analyzed using a matrix. The matrix format followed a structure previously used by Eschenfelder and Gavalas (2017) by considering individual articles on the basis of study design; level of evidence, when applicable; number of subjects and demographics; interventions; measured outcomes and assessments used; and findings and results. The third and final round of exclusion in this study was the most selective, as articles were excluded for further analysis if they (a) were published prior to the year 2000, (b) were purely informative articles, (c) studied interpretation of art in any way, (d) included fewer than three participants, or (e) used art modalities not feasible to use during an initial evaluation to construct an occupational profile.…”
mentioning
confidence: 99%